Pengaruh Kesejahteraan terhadap Kepuasan Kerja Pegawai Tidak Tetap (PTT) di Kantor Kecamatan Tanah Grogot - Ernawati Ernawati; Novi Riyani; Norwahidah Norwahidah; Sri Wahdaningsih; Hainun A; Setio Jatmiko (Pusat Riset dan Inovasi Nasional, 2025)
The purpose of this study was to determine the effect of welfare (X) on job satisfaction of non-permanent employees (Y) at the Tanah Grogot District Office. This study is a population study, namely using the entire population as a sample, namely 30 non-permanent employees, while the data collection methods used are questionnaires, observations, interviews, and library research. Based on the results of the simple linear regression analysis conducted, this study concludes that individually (partially) the independent variable, namely welfare, has a significant and positive effect on the dependent variable, namely employee job satisfaction. This is evidenced by a simple linear regression equation: Y = -2.998 + 0.708X The results of the simple correlation coefficient analysis obtained R of 0.911, meaning that there is a very strong correlation between welfare (X) and employee job satisfaction (Y) at the Tanah Grogot District Office. The coefficient of determination (R2 Square) of 0.829 means that around 82.9% of welfare (X) is influenced by the variable Job Satisfaction (Y). While the rest is influenced by other factors not included in this study by (100-82.9)% = 17.7%. Furthermore, the results of the partial test (t-test) show the t-count value for the welfare variable (X) of 11.666 which when compared to the t-table of 2.04841, then welfare (X) has an effect on employee job satisfaction (Y) at the Tanah Grogot District Office, the t-count value is > t-table..